Election Of The Head Of The Study Program By Applying The SAW Method (Case Study STMIK Pelita Nusantara) - Bosker Sinaga; R. Mahdalena Simanjorang (Sean Institute, 2020)
The election of the Head of the Study Program is very important to consider the maximum results of services to students. In the process of selecting the Head of the Study Program at STMIK Pelita Nusantara, they usually directly appoint those who occupy the position with several elements. Determination of the Head of the Study Program is very necessary by making some general and specific criteria and expertise in their fields. The system that is needed is the Decision Support System for the Head of Study Program Decision. The variables specified in this study are 1) General which includes: Functional Position, Status, Expertise. 2) Specifically covering: Attitude Value, General Knowledge Test Value, Field Knowledge Test Value, and Interview. This system was built by applying the web-based Simple Additive Weighting (SAW) method and MySQL as the database